Partnerships and Production Chains: A Development Alternative for the Municipality of Yopal, Casanare - Cáceres Gómez, Luz Stella; Pardo Enciso, Claudia Esmeralda; Torres, Alicia Milena (Cooperativismo & Desarrollo, 2014)
This study was conducted by Grupo Lasallista de Economía Solidaria (gles) of Universidad de La Salle , in the project titled “Alternative organization for agricultural and tourism production in Yopal, Casa- nare”. This is linked with the “Human biosettlement for a new rural region” program which contributes to the organization of small and medium agricultural producers and the creation of dynamic growth in tourism through associative forms in agricultural production chain organizations in Yopal, Casanare. This work is conducted with a focus on new rural areas, looking towards 2014. The analysis examines production in Yopal, and the configuration of production chains with an associative basis and viable strategy, taking into account the region’s relative advantages, the impact of oil production in the pro- duction, social, cultural and economic dynamic of the municipality, as well as the national and regional political framework that demonstrate the government’s approach to promoting economic and social development of the country and the regions supported by dynamic agriculture and tourism.